2022
DOI: 10.1111/exd.14570
|View full text |Cite
|
Sign up to set email alerts
|

Secretomes as an emerging class of bioactive ingredients for enhanced cosmeceutical applications

Abstract: Skin ageing is predominantly caused by either intrinsic or extrinsic factors, leading to undesirable skin features. Advancements in both molecular and cellular fields have created possibilities in developing novel stem cell‐derived active ingredients for cosmeceutical applications and the beauty industry. Mesenchymal stromal cell (MSC)‐derived secretomes or conditioned media hold great promise for advancing skin repair and regeneration due to the presence of varying cytokines. These cytokines signal our cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 95 publications
0
8
0
Order By: Relevance
“…In particular, the results of previous in vitro studies and preclinical or clinical applications have suggested that the retention of cellular viability or the presence of the original cellular structures was not required to conserve specific therapeutic functions [ 31 , 32 , 38 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ]. Therefore and as mentioned above, further potential applications inspired by dermal progenitor cytotherapies comprise the topical use of cell-derived cell-free biological complexes (e.g., cell secretomes, exosome fractions) in cutaneous regenerative medicine [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the results of previous in vitro studies and preclinical or clinical applications have suggested that the retention of cellular viability or the presence of the original cellular structures was not required to conserve specific therapeutic functions [ 31 , 32 , 38 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ]. Therefore and as mentioned above, further potential applications inspired by dermal progenitor cytotherapies comprise the topical use of cell-derived cell-free biological complexes (e.g., cell secretomes, exosome fractions) in cutaneous regenerative medicine [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, SCM has been shown to contain a number of growth factors and cytokines that may contribute to the beneficial effects of SCM (54,55). Recent studies have also shown that SCM contains microvesicles or extracellular vesicles (EVs) and that the EVs obtained from MSCs exert beneficial effects by transferring biological cargo, including cytoskeleton proteins, signaling proteins, lipids, enzymes, transcription factors, mRNA, microRNAs, long non-coding RNAs, DNA and metabolites, to host cells (56,57). However, the exact factors responsible for the effects observed in the present study remain unknown and require further investigation (54).…”
Section: Discussionmentioning
confidence: 99%
“…Further, it is reported that in a mouse model, injected ADSCs survived for 28 days, suggesting the possible long-term active life of ADSCs in injected skin. In addition, a conditioned medium known as secretome, which contains extracellular vesicles, such as exosome, is reported to have a variety of biological activities for skin repair and rejuvenation [12]. Secretome isolated from ADSCs contains a wide range of cytokines and growth factors that are beneficial in reversing aged skin symptoms by inducing epidermal keratinocyte, dermal fibroblast activation, and proliferation [13].…”
Section: Discussionmentioning
confidence: 99%